ANTIVIRAL EFFECTS OF GREEN TEA (Camellia sinensis) AGAINST PATHOGENIC VIRUSES OF HUMAN AND ANIMALS (A MINIREVIEW) - Mahmood, Muhammad Shahid Mahmood; Mártinez, José L.; Aslam, Azhar; Rafique, Azhar; Vinet, Raúl; Laurido, Claudio; Hussain, Iftikhar; Abbas, Rao Zahid; Khan, Ahrar; Ali, Shahid (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Tea is the second most addictive worldwide after formulations containing caffeine in carbonated beverage. Green tea ismade from leaves of the Camellia sinensis plant. In the repertoire of traditional Chinese medicine, green tea beverages have played afundamental role associated with their culture. It has been suggested that green tea has a number of positive health benefits that arereviewed and discussed in this minireview.Materials and Methods: We performed a search using the key words “green tea” AND “antiviral” covering the last 10 years. Theconsulted data based were PubMed, ISI Web of Knowledge, Scopus, Reuters and Thomson.Results: The results of the searching greatly support that green tea presents both antibacterial and antiviral effects. The beneficial effectsof green tea are mainly attributed to the presence of a type of polyphenols known as catechins and formed by several isomers including(-) - epigallocatechin gallate (EGCG), (-) - epigallocatechin, (-) - epicatechin gallate, (-) -epicatechin, and (+) - catechin. The catechins ingreen tea have a wide range of antiviral activity against a variety of viruses that act by interfering with its replication cycle.Conclusion: A detailed information on the antiviral activity of green tea in a number of different viruses show a promising future as apopular drink and also as a potential therapeutic agent.